Հայկական վիշապամարտի երկու հակադիր կերպարներ - Արմեն Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
1. Слово k‘aĵ (кадж) «лучший, храбрый» был эпитетом бога войны Ваагна. Каджами называется также группа духов, которые в древности должны были быть последователями бога Ваагна. Каджи сравниваются с марутами и рудрами, последователями бога Индры в индийской мифологии. Слово кадж этимологически сравнимо с индийским swadhā, эпитетом марутов. 2. В армянской мифологии Змей-вишап преграждает космические воды. Этот образ известен и у других народов – например, в индийской мифологии Змей, противник бога Индры, называется Вритра – «затор, преграда». В древнем эпосе «Випасанк» соперником героев выступает драконид Аргаван/Аргам. Это имя, независимо от реальной этимологии, могло осмысляться в связи с армянским корнем arg(el)- «затор, преграда». 1. The word k‘aĵ “best, brave“ was the epithet of the Armenian war god Vahagn. Also, the same term designates a group of (evil) spirits, which in antiquity would have been regarded as the followers of Vahagn. The k’aĵs have been compared with the Maruts and the Rudras, the followers of the god Indra in Indian mythology. Their name may be etymologized in connection with Ind. swadhā, epithet of the Maruts. 2. In Armenian mythology, the Serpent-Vishap blocks the cosmic waters. This figure is known in other traditions as well, e.g., in Indian mythology, the Serpent, adversary of Indra, is called Vrtra – “barrier, obstacle.“ In the ancient epic Vipasank‘, Argawan/Argam the dragonid figures as the adversary of the heroes. This name, regardless of its real etymology, might have been conceptualised by Arm. arg(el)- “barrier, obstacle.“
Keywords: Literature; Language and Literature; G Geography; Anthropology; Recreation; GR Folklore